Confined PdMo Ultrafine Nanowires in CNTs for Superior Oxygen Reduction Catalysis. Issue 26 (30th May 2022) - He, Qianqian; Xu, Tengfei; Li, Jiajie; Wang, Jialong; Jin, Chunqiao; Chen, Qian; Gu, Xiaokang; Wang, Xingguo; Wei, Juntian; Duan, Huiping; Gong, Yongji
Abstract: One‐dimensional (1D) ultrafine nanowires of different materials, especially noble metals, present an enticing prospect for catalyst applications due to their numerous active sites exposed. However, the controllable synthesis and stability issues hinder their practical applications. Herein, single‐walled carbon nanotubes (SWCNTs) are adopted as the template to synthesize and stabilize ultrafine nanowires of metals. Furthermore, the oxygen reduction reaction (ORR) is employed as an application demonstration. Impressively, the as prepared PdMo nanowires exhibit a half‐wave potential of 0.923 V and the mass activity is 35 times and 130 times higher than those of commercial Pt/C and Pd/C catalysts, respectively. Because of the protection, a superior ORR durability with 50 000 cycles can be achieved. Density functional theory (DFT) calculations reveal that the SWCNTs surface can be activated by the encapsulated PdMo NWs to achieve the exclusive adsorption of O2 and the following reduction reaction. In addition, PdMo NWs@SWCNTs demonstrate excellent catalytic performance as the cathode of lithium‐oxygen batteries. The cell can reach a high discharge capacity of over 10 000 mAh g −1, better than most of the former reported catalytic electrodes. The tailored design PdMo NWs@SWCNTs show widespread applications in various energy storage & conversion fields. Abstract : In this work, confined ultrafine metal nanowires are synthesized inside carbon nanotubes and they show outstanding catalytic activity and excellent cyclic stability in the oxygen reduction reaction and when used as the cathode of Li–O2 batteries. Density functional theory calculations reveal that the carbon layer can be activated by the encapsulated metal nanowires to achieve the exclusive adsorption of O2 and the following reduction reaction.